Strategies for Embedding Research Data Management Through Effective Communication - Fadwa Alshawaf (Data, 2025)
Effective research data management (RDM) is essential for ensuring research integrity, reproducibility, and compliance with FAIR principles. Despite the development of comprehensive RDM frameworks, many institutions still struggle to ensure widespread engagement and compliance among researchers and staff. Adoption of RDM practices remains slow due to limited awareness, unclear benefits, and perceived administrative burdens. Using Mendelow’s Matrix, this study draws on survey data to map key stakeholders, such as researchers, RDM professionals, institutional leadership, funding bodies, and infrastructure providers, based on their power and interest to ensure developing tailored communication strategies. This paper presents a communication strategy to enhance RDM adoption by improving visibility, fostering engagement, and encouraging the integration of RDM into research workflows and curricula. It outlines key approaches, including awareness campaigns, targeted publishing, strategic partnerships, and knowledge-driven promotion to embed RDM into research workflows.